Catalytic Dehydration of Glycerol to Acrolein in a Two-Zone Fluidized Bed Reactor - Katryniok, Benjamin; Meléndez, Roger; Bellière-Baca, Virginie; Rey, Patrick; Dumeignil, Franck; Fatah, Nouria; Paul, Sébastien (Frontiers in Chemistry, 2019)
The gas-phase catalytic dehydration of glycerol to acrolein was carried out in a Two-Zone Fluidised-Bed Reactor (TZFBR) using a 20 wt.% phosphotungstic acid (H3PW12O40) catalyst supported on CARIACT-Q10 commercial silica. In a first step, a hydrodynamic study of the reactor was performed. A quality of fluidisation of more than 80% was obtained. In a second step, the mechanical stability of the catalyst was studied. It was found that only the external layer of active phase is eliminated under the conditions of operation whereas the global composition of the catalyst was not significantly affected after 44 h of fluidisation. Finally, in a third step, the influence of the main operating parameters on the overall catalytic performances (glycerol/oxygen molar ratio and relative volumes of the reaction and regeneration zones) was investigated showing notably the importance of the O2/glycerol ratio, resulting in an inverse trend between conversion and selectivity. Increasing O2/glycerol ratio led to higher conversion (lower coke deposit as shown by TGA analysis), but to the detriment of the selectivity to acrolein, supposedly due to the presence of O2 in the reaction zone causing the degradation of glycerol and acrolein.